Remote collaborative learning support system using avatars with facial expressions. (2018) - Okubo, Masashi; Komatsu, Shinya
Recently, various researches have been conducted about remote collaborative learning. However, unlike face-to-face communication, remote communication is difficult to give nonverbal information such as facial expression and physical. Therefore, it may interfere with the transmission of intention and emotion. In this research, to support intention and emotion transmission in remote collaborative learning, we develop and assess a remote collaborative learning support system using avatar with facial expression on sharing note system. We create 13 types of avatar with facial expression with reference to Russell's emotional circle model. As a result of comparative experiments with and without avatar with facial expression, the drawing time has increased and the test score is higher when there are facial expressions. And since weak positive correlation is observed between the drawing time and the test score, it is presumed that the avatar with facial expression promotes explanatory activities by drawing and enhances the learning efficiency.